Dampak Uniformity Terhadap Informasi Akuntansi: Sebuah Kajian Literatur - Rahmawati, Ulfa (Balance: Media Informasi Akuntansi dan Keuangan, 2024)
Along with the development of the world economy, accounting also continues to develop. The accounting evolution process cannot be separated from public criticism and suggestions. One of these criticisms is uniformity. Uniformity is the level of similarity in financial reporting of companies within a country and even between countries in the world. This research seeks to examine the impact of uniformity on accounting information by conducting a review of previous literature. The results of the study show that uniformity will create comparability of financial reports so that financial reports become relevant and faithful representation and will make it easier for users to make decisions.